Moral and scientific boundaries: research ethics on the Thai–Burma border - Parker, Michael J (Journal of medical ethics, 2012)
Developing good practice in consent The variety of languages spoken in the region, the range of values and beliefs, and the inevitable constraints on access to education mean that the process of consent and the development of consent-related materials is a challenge and may require translation between a number of different languages. 3 The complexity of the scientific terms such as 'genomics' and processes such as data sharing is difficult to convey in meaningful terms. 4 In addition to issues related to understanding, it may be very difficult for research subjects to refuse to participate in research when it is carried out by a research centre that is also their main provider of healthcare.